Functional Connectivity of EEG Signals Under Laser Stimulation in Migraine - de Tommaso, Marina; Trotta, Gabriele; Vecchio, Eleonora; Ricci, Katia; Van de Steen, Frederik; Montemurno, Anna; Lorenzo, Marta; Marinazzo, Daniele; Bellotti, Roberto; Stramaglia, Sebastiano (Frontiers in Human Neuroscience, 2015)
In previous studies migraine patients showed some abnormalities of pain related evoked responses, as reduced habituation to repetitive stimulation. In this study we aimed to apply a novel analysis of EEG bands synchronization and directed dynamical influences under painful stimuli in migraine patients compared to non migraine healthy volunteers. Thirty-one migraine without aura outpatients (MIGR) were evaluated and compared to 19 controls (CONT). The right hand was stimulated by means of 30 consecutive CO2 laser stimuli. EEG signal was examined by means of Morlet wavelet, synchronization entropy and Granger causality, and the statistic results embedded into a scalp model. The vertex complex of averaged laser evoked responses (LEPs) showed reduced habituation compared to controls. In the pre-stimulus phase enhanced synchronization entropy in the 0, 5-30 Hz range was present in MIGR and CONT between the bilateral temporal parietal and the frontal regions around the midline. Migraine patients showed an anticipation of EEG changes preceding the painful stimulation compared to controls. In the post-stimulus phase, the same cortical areas were more connected in MIGR vs CONT. In the totality of patients and controls, the habituation index was negatively correlated with the Granger Causality scores. A different pattern of cortical activation after painful stimulation was present in migraine. The increase in cortical connections during repetitive painful stimulation may subtend the phenomenon of LEPs reduced habituation. Brain network analysis may give an aid in understanding subtle changes of pain processing under laser stimuli in migraine patients.